THE DEVELOPMENT OF PRE-SERVICE SCIENCE TEACHERS’ REFLEXIVE PRACTICE AT THE LEBANESE UNIVERSITY FACULTY OF EDUCATION - CHATILA, Hanadi; ABOU ALI, İman (The Eurasia Proceedings of Educational and Social Sciences, 2016)
A major aim in teacher’s preparation program is to promote reflective practice among future teachers. Literature in teacher education points out to the importance of reflection in the development of quality teaching (Coffey 2014; Jay & Johnson, 2002; Perrenoud 2012). Schon’s (1983,1987), proposed a conceptual framework about reflective practice that involves two phases of reflection: reflection-on-action which refer to the reflection after doing the action anf reflection-in-action which occurs during the doing. The framework was adapted later to include reflection for action, that takes place before the doing of the action as the teacher reflects about the future experience informed by the past practice. The current study, aims to explore if the training program at the Lebanese University, Faculty of education, prepare reflective primary science teachers, on the basis of Schon’s (1983,1987) framework. For this purpose a convenience sample of 30 participants from third year primary science pre-service teachers was selected to participate in the study along with their five trainers. Both quantitative and qualitative method including questionnaire, interviews, curriculum and reflection report analysis were used in the study. The results show that pre-service teachers develop to some extent “reflection-for-action” and “reflection-in-action”, however they lack strategies for the “reflection on- action” as they face difficulties in regulation and self-improvement.